11. EVALUATION OF TREATMENT RESULTS OF BENIGN PROSTATIC HYPERPLASIA, AT THE NATIONAL REHABILITATION HOSPITAL FROM 2022 TO 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: The aim of this study is to describe the treatment outcome for benign prostatic hyperplasia at National Nursing Rehabilitation Hospital from 2022 to 2023.Topics and methodologies: The National Nursing Rehabilitation Hospital administered treatment to 63 patients who presented with benign prostatic hyperplasia. Descriptive cross-sectional study with longitudinal follow-up: Age, benign prostatic hyperplasia characteristics, comorbidities, IPSS score, quality of life score, and Permixon effects are study characteristics.The results were: The mean age of the patients was 64.79±11.62 years (46-84) years, with 45.03 percent of the patients being aged 70 years or older. Benign prostatic hyperplasia is frequently accompanied by urinary tract infections, which comprise the majority (77.78%) of these conditions. The majority of patients (41.27%) urinated frequently n=9 times/24 hours; the majority of patients urinated at night 5 times/day (41.27%), with an average frequency of 4.05±0.89 urinations per day; residual urine volume of 123.81±34.71 lst; total input IPSS score of 30.59±2.23 points, with 100% at the severe level; quality of life score of 4.70±0.66 (4-6 points); and SHIM scores between age groups at severity levels, with Benign Prostatic Hyperplasia patients having a significantly affected SHIM scores. The patients’ quality of life has markedly improved following treatment, as an evidence by a statistically significant difference (p < 0.05).Conclusion: Patients with benign prostatic hyperplasia often show signs of urinary disorders, especially frequent urination at night, affecting quality of life by causing insomnia. Combining Permexon treatment with the general treatment regimen provides good response and reduces the patient’s stay at work, improving quality of life.
Keywords: Prostate hyperplasia, urinary disorders, IPSS score.